Pengaruh Kehadiran Apoteker Terhadap Pelayanan Kefarmasian di Apotek di Kota Padang - Dwi Dominica; Deddi Prima Putra; Yulihasri Yulihasri (Jurnal Sains Farmasi & Klinis, 2016)
Standard pharmacy services is measure used especially in implementing pharmacist pharmacy services. This study examines effect of presence of Pharmacists to pharmacy services, is crosssectional study using questionnaires in February - August2015. The research sample 90 Pharmacists in pharmacies taken random. results Showed the percentage of the presence of the pharmacist in the pharmacy Padang city 58.67% and Pharmaceutical Services Categorized less (inspection recipe 57.06%, 55.12% prescription preparation, and delivery prescriptions 51.89%) with average percentage 54,69%. Linear regression analysis of test results can be known effect X on Y positive. Testing shows the product moment correlation coefficient X to Y Strong where: r=0.910, in testing the coefficient of determination shows X higher influence on Y equal to 82.8% and 17.2% influenced other factors. Based on the F test 422,579 with significance of 0.000. Due significant levels <0.05, can concluded that the presence of Pharmacists have influence on Pharmaceutical Services.